1980
DOI: 10.1042/bj1880381
|View full text |Cite
|
Sign up to set email alerts
|

High concentration of RNA polymerase I is responsible for the high rate of nucleolar transcription

Abstract: When isolated rat liver nuclei and nucleoli are compared for RNA synthesis in vitro, the rate of nucleolar RNA synthesis is found to be more than 10 times higher. In order to understand this high rate of nucleolar transcription, DNA from both nuclear and nucleolar fractions was isolated and compared for the ability to direct RNA synthesis with homologous RNA polymerases. No difference between these two templates is evident. On the other hand, when the total nuclear and nucleolar RNA polymerases are isolated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…57, 58 In the nucleolus, for example, membrane-less compartmentalization is known to concentrate RNAP I and boost the transcription rate. 59 A recent study demonstrates upregulation of hyperphospholyration of RNAP II upon membrane-less compartmentalization through LLPS of kinase proteins in nuclear speckels. 60 Such reaction acceleration by enzyme sequestration is traditionally assumed to be due to co-localization and better proximity between the enzyme and its reaction partners.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…57, 58 In the nucleolus, for example, membrane-less compartmentalization is known to concentrate RNAP I and boost the transcription rate. 59 A recent study demonstrates upregulation of hyperphospholyration of RNAP II upon membrane-less compartmentalization through LLPS of kinase proteins in nuclear speckels. 60 Such reaction acceleration by enzyme sequestration is traditionally assumed to be due to co-localization and better proximity between the enzyme and its reaction partners.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that membraneless organelles composed of protein–protein or protein–nucleic acid complexes are prevalent in the nucleus and cytoplasm and linked to protein aggregation-related diseases, cancer, and stress response. , In the nucleolus, for example, membraneless compartmentalization is known to concentrate RNAP I and boost the transcription rate . A recent study demonstrates upregulation of hyperphospholyration of RNAP II upon membraneless compartmentalization through LLPS of kinase proteins in nuclear speckles .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Bar = 0.2 ~. and released from isolated nuclei upon incubation in isotonic buffers (about 20% of rat liver RP I exists in the free form; Yu, 1980; see also Jacob and Rose, 1978). Furthermore, the observation that addition of exogenous DNA templates to nucleoli isolated under conditions minimizing RP I leakage stimulates RNA synthesis, also argues against a stable association of the free RP I to nucleolar structures (see Grummt, 1978;Muramatsu et al, 1979) (Coupar and Chesterton, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Labeling methods for incorporating markers can be used to estimate the presence of RNA. Radioactive isotopes of hydrogen, carbon, and phosphorus can be incorporated to the cell culture system, and the cells produce RNA containing the corresponding isotope for identifiable measurements (Mukherjee and Beermann, 1965;Yu, 1980;Huang and Szostak, 1996). However, the exact time required for the added isotopes to be transported into the cell and become part of the newly transcribed RNA is difficult to determine.…”
Section: The Availability Of Information For Identifying Rna Agementioning
confidence: 99%